Brazil Between Global Recognition and Neutrality over the Russian War Against Ukraine - Tabosa, Clarissa (Journal of Regional Security, 2023)
This contribution investigates what explains Brazil’s narrative of neutrality in times when neutrality means support for Russia. Brazil’s neutrality narratives can be seen as a consequence of the economic interests of the Brazilian agrobusiness, highly dependent on Russian fertilizers, but also due to its historical tradition of diplomatic neutrality. However, neutrality seems to clash with Brazil’s self-conceptualization of its identity as a relevant player on the international level, especially since the 2000s. Furthermore, I reflect on the implications of Brazil’s narratives following the election of Lula da Silva for Brazil and on how LA might position itself in the near future as this war continues.